That Province needs not only a Governor, but a Colonel of Dragoons: the Portuguese Borderland Commanders and the government of the captaincy of Rio Grande de São Pedro, 18th century (Ágora Journal, 2021)
The paper approaches the role known as Borderland Commander (Comandante de Fronteira), which operated in the captaincy of Rio Grande de São Pedro during the 18th and 19th centuries. Analysing his duties and the degree in which he could interfere on the society the paper discusses strategies of government and territorialization for the Portuguese empire during the second half of the 1700’s. As an office non-identified for other spatial realities on Portuguese empire it searches to link the Borderland Commanders with Iberian traditions for civil and military government. For this purpose, the paper discusses the orders and instructions sent by the governor of the captaincy seeking to understand how the government and territorial administration were stablished.
Keywords: borderland; government; territory